Social network analysis to support decision-making - Freire, Manuela (2022)
The growing importance of decision-making within web context requires defining and implementing efficient mechanisms to support its activities. The social networks, seen as opportunities for organizational collaboration, allow people to interact across continents and time zones, expressing opinions and sharing information. They also constitute an increasingly used means for decision support, when seeking information, which can produce a massive amount. Therefore, it is necessary to analyze such information in order to establish opinions and points of view on a variety of issues that can play an important role for decision-making. As the web discourses (of opinion and information) often encompass knowledge construction, interaction and the consequent development of online social networks capturing and understanding all interactions can be extremely valuable for building indicators to support decision-making. Accordingly, the main objective of this work is to explore the interactions and discursive exchanges between social actors, in order to extract information towards decision support. We intend to investigate whether it is possible to structure collected data from online social networks, integrating human interaction and network structure, namely by using Social Network Analysis (SNA) to study the network from a duofold manner: the web discourse, which depends on the transmition of information; and the interaction among social actors, as information disseminators. Our work intends to determine whether social actors and their interactions are consistent with the creation of indicators fit for decision support.